The Effect of Training Programs, Emotional Intelligence on SME Business Performance and Competence as Intervening Variables - Edi Sugiono (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The economic functions of this sector include providing goods and services for consumers with low to moderate purchasing power, contributing more than half of economic growth and contributing to the country's foreign exchange earnings. Socio-politically, the function of this sector is also very important, especially in the absorption of labor and efforts to eradicate poverty. In addition, small businesses are a basic need for our country that adheres to a populist system. Therefore, more attention should be paid to the business performance of SMEs, because SMEs are the largest contributor to the country's GDP. The purpose of this study is to analyze the effect of the training program, emotional intelligence on SME business performance and competence as an intervening variable, with data analysis using the Structural Equation Model (SEM) program through the AMOS software. The results show that training programs, emotional intelligence and competence have a positive and significant impact on SME business performance and training programs and emotional intelligence have a positive and significant impact on competence and competence to mediate the effect of training programs and emotional intelligence on SME business performance.